2001
DOI: 10.1128/iai.69.10.6055-6063.2001
|View full text |Cite
|
Sign up to set email alerts
|

Population Dynamics of Streptococcus mitis in Its Natural Habitat

Abstract: The purpose of this study was to examine the genetic structure of the typical commensal Streptococcus mitis biovar 1 in its natural habitat in the human oral cavity and pharynx and to investigate the role that selected microbial properties and host, spatial, and temporal factors play in determining the structure of the bacterial population. Consecutive samples were collected from buccal and pharyngeal mucosal surfaces of two infants, their four parents, and two elderly individuals over a period of approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
72
3
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(89 citation statements)
references
References 50 publications
9
72
3
2
Order By: Relevance
“…The identity of the ribotype and age (months) of the infant at which the saliva was collected are indicated at the bottom of each column. and replacement of S. mitis (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005), we hypothesized that the concentration of S. mitis-specific SIgA antibody in saliva is limited because the mucosal immune system has a very short exposure to the individual clones of S. mitis that appear and rapidly disappear from the mouth. Under these conditions, it might be expected that the secretory immune system would respond to those antigens that are common to every clone of S. mitis because these provide a 'stationary target'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The identity of the ribotype and age (months) of the infant at which the saliva was collected are indicated at the bottom of each column. and replacement of S. mitis (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005), we hypothesized that the concentration of S. mitis-specific SIgA antibody in saliva is limited because the mucosal immune system has a very short exposure to the individual clones of S. mitis that appear and rapidly disappear from the mouth. Under these conditions, it might be expected that the secretory immune system would respond to those antigens that are common to every clone of S. mitis because these provide a 'stationary target'.…”
Section: Discussionmentioning
confidence: 99%
“…In parallel with our studies on the salivary mucosal immune response to commensal oral bacteria, we and others have examined the population dynamics of S. mitis biovar 1 in the mouth and have shown that, while this bacterium is stable at the species level, it exhibits significant clonal turnover and replacement (Hohwy and Kilian, 1995;Fitzsimmons et al, 1996;Hohwy et al, 2001;Kirchherr et al, 2005). Indeed, most of the clones in the current study were isolated at a single sampling visit and could not be re-isolated at the successive visit, 2 months later.…”
Section: Introductionmentioning
confidence: 99%
“…They are highly acidogenic, producing short-chain acids which soften hard tissues of teeth. Three isozymes of glucosyltransferases catalyze and metabolize sucrose to synthesize insoluble extracellular polysaccharides, which increase their adherence to the tooth surface and persuade biofilm formation [6,68,69]. The most significant mutans streptococci isolated from tooth caries samples are S. mutans [6] and S. sobrinus.…”
Section: Mutans Streptococci (Ms)mentioning
confidence: 99%
“…The persistence of clones appears to vary for different species, with many clones simultaneously inhabiting the oral cavity at different periods. Genomic polymorphisms within bacterial strains along with the response of the host will determine the disease situation and progression in the individual patient (Hohwy et al, 2001;Kononen et al, 1994;Tambo et al, 2010). Early colonising species showing wide clonal diversity (reflected in antigenic variety) elicit natural immunity which benefits the host, while frequent turnover of clones within a particular host may allow the species to overcome the host response and exert its pathogenicity (Smith, 1988).…”
Section: Gene Expressionmentioning
confidence: 99%